Laboratory safety evaluation at the Ethiopian Public Health Institute, 2018-2019 - Stephanie Ringler; Emily G. Pieracci; Sylvia Murphy; Asefa Deressa; Fatuma Yassin Bushra; Theresa Kanter; Getnet Yimer; Lillian A. Orciari; Mary Reynolds; Lauren Greenberg (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background In 2015, Ethiopia designated rabies as a priority zoonotic disease. Challenges in rabies diagnostic capacity, including laboratory safety, were identified in 2016. As a pilot evaluation, the national rabies laboratory in Ethiopia (EPHI) was chosen to participate in an evaluation of necropsy laboratory facilities and procedures which was conducted over two years. This evaluation identified areas for improvement that strengthening would enhance safety in the laboratory environment. Process changes, specifically in cleaning procedures, will decrease the likelihood of cross contamination and improve precision of testing. # Methods This evaluation consisted of two sections: a 38-question verbal interview and an observational evaluation of necropsy laboratory practice. In March 2018, we evaluated EPHI's laboratory biosafety procedures, and the laboratory technicians' knowledge, practices, and attitudes in the animal necropsy laboratory before CDC-led laboratory trainings (September and December 2018). A post-training evaluation was conducted in March 2019. # Results Safety compliance scores in 2019 were noticeably increased from 2018. Interview scores increased from 57% to 91% and laboratory observation scores increased from 74% to 91%. # Conclusion This evaluation revealed that a necropsy laboratory assessment could be a valuable tool for understanding challenges faced by laboratories performing rabies diagnosis in Ethiopia. Assessment materials help to identify on-going challenges as well as areas of improvement in a systematic manner. In the future, this assessment could be used as a model for labs performing rabies diagnosis in a decentralized system. Additional rabies laboratories are anticipated to stand up throughout Ethiopia and laboratory assessments based on this methodology could provide valuable insights into how to mitigate risks.